The Internalization of Islamic Values in Guiding Students’ Morality Through The Subjects of Aqeeda Akhlaq at Madrasah Aliyah Al Ikhsan Jombang - Naily Rahma (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2017)
Keywords: Islamic Values, Morals guidance, Internalization The formulation of the problem in this research are, firstly, how is the implementation of internalization of Islamic values in guiding students morality through the subjects Aqeeda Akhlaq at Madrasah Aliyah Al Ikhsan Jombang? Second, what are the supporting and inhibiting factors of the internalization of Islamic values in guiding students’ morality through the subjects Aqeeda Akhlaq at Madrasah Aliyah Al Ikhsan Jombang? Third, how is the efforts made by teachers in Madrasah Aliyah Al Ikhsan Jombang in overcoming the obstacles of the internalization of Islamic values in guiding students morality through the subject of Aqeeda Akhlaq?Qualitative approach is used in this research. Data are collected through observation, interview and documentation. The data is analyzed using descriptive analysis which described "what is" about a variable, symptom or state.Based on the results of this study, it can be concluded that, first, the implementation of the internalization of Islamic values in guiding students morality through the subjects Aqeeda Akhlaq in the madrasah was shown by the existence of religious activities that must be implemented/ obeyed by all the students in the madrasah, whether it is in the form of Mahdhoh and Ghoiru Mahdhoh. Second, the supporting factors in the implementation of internalization of Islamic values in guiding students morality through the subjects Aqeeda Akhlaq in this madrasah consists of internal and external factors that exist in the child himself. Meanwhile, the factors that hinder the implementation of the internalization of Islamic religious values in guiding students morality through the subjects Aqeeda Akhlaq in this madrasah is generally a constraint that come from students who had many problems which is difficult to set up, lazy to perform the task and so on. Other factor is families relying solely on education and guidance provided by the school, and problems BP teachers who had not been able to handle the problems that were done by students. Third, in overcoming the obstacles of internalization of Islamic religious values in guiding students morality through the subjects Aqeeda Akhlaq, efforts made by principals and teachers are: (1) giving more attention to troubled children, (2) giving understanding gradually, (3) providing a fair affection among students.